Comparing common doses (double-dose vs usual-dose) of atorvastatin for preventing contrast-induced acute kidney injury and mortality after coronary angiography. Issue 30 (July 2017) - Bei, Wei-Jie; Chen, Shi-Qun; Li, Hua-Long; Wu, Deng-Xuan; Duan, Chongyang; Chen, Ping-Yan; Chen, Ji-Yan; Tan, Ning; Xie, Nian-Jin; Liu, Yong
Abstract : Abstract: High-dose atorvastatin pretreatment was proved reducing the risk of contrast-induced acute kidney injury (CI-AKI), especially in patients with high C-reactive protein (CRP) levels. We evaluated the effects of common atorvastatin doses (double vs usual) on the risk of CI-AKI and mortality. We recorded outcomes from 1319 patients who were administered periprocedural common doses of atorvastatin. The risks of CI-AKI and mortality between double-dose (40 mg/d) and usual-dose atorvastatin (20 mg/d) were compared using multivariable regression models in all patients or CRP tertile subgroups. Seventy-six (5.8%) patients developed CI-AKI. Double-dose atorvastatin compared with usual-dose did not further reduce the risk of CI-AKI (adjusted odds ratio [OR]: 2.28, 95% confidence interval [CI]: 0.92–5.62, P = .074), even for patients in the highest CRP tertile (>8.33 mg/L; adjusted OR: 3.76, 95% CI: 0.83–17.05, P = .086). Similar results were observed in reducing mortality in all patients (adjusted hazard ratio: 0.47, 95% CI: 0.10–2.18; P = .339) and in the highest CRP tertiles ( P = .424). In the subgroup analysis, double-dose atorvastatin increased risk of CI-AKI in patients with creatinine clearance (CrCl) < 60 mL/min, anemia, contrast volume > 200 mL and > 2 stents implanted ( P = .046, .009, .024, and .026, respectively). Daily periprocedural double-dose atorvastatin was not associated with a reduced risk of CI-AKI compared with usual-dose, and did not provide an improved long-term prognosis, even in patients with high CRP levels. However, it increased the risk of CI-AKI in patients with a high contrast volume/CrCl.